22 What can we learn from patients who died from SARS-CoV2 following escalation to a respiratory high dependency unit for trial of non-invasive respiratory Support?. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Shoulder, Richard; Evans, Sarah; Elder, Patrick; Sundaralingam, Anand; Kewalramani, Namrata; Flight, William; Hardinge, Maxine; Rahman, Najib; Miller, Mary
Abstract : SARS-CoV-2 is associated with significant risk of death, particularly in older patients and those with comorbidities. Emerging evidence supports use of non-invasive respiratory support; however, it is uncertain whether and when this should be stopped in patients who fail to respond to treatment. The experience of teams caring for awake patients who died from SARS-CoV2 infection on Non-Invasive Respiratory Support in a Respiratory High Dependency Unit has not been documented. This was a retrospective study of 33 adult patients who died of SARS-CoV2 on the Respiratory High Dependency Unit at the John Radcliffe Hospital, Oxford between 28/03/20 and 20/05/20. The population had multiple comorbidities (median Charlson Index 5 (IQR 4–6); median age 78 (IQR 72–85)) and respiratory support was trialled in all but one case, with CPAP the most common form (84.8%). Median time to death was 10.7 days from symptom onset (IQR 7.52–14.6), 4.8 days from hospital admission (IQR 3.1–8.3) and 21.5 hours from documented decision to cease active treatment. 48.5% of patients remained on respiratory support at the time of death, the reasons for this included ongoing active treatment (n=8), patient distress (n=6), awaiting further family discussions (n=1) and was undocumented in one case. Data collected included: demographic and comorbidity data; timings of symptom onset and disease course; use of respiratory support; community and hospital Advance Care Planning; palliative care input and medication use and communication with families. Non-Invasive Respiratory Support may play a key role in symptom management in select patients, however, further work is needed in order to identify patients who will most benefit from Respiratory Support and those for whom withdrawal may prevent unnecessary distress at the end of life or potential prolongation of suffering. For those with a poor prognosis early assessment of palliative needs and premorbid wishes should be encouraged.